Propagation of antibacterial cold atmospheric pressure plasma through small-bore tubing - Elanie F. Briggs; Bhagirath Ghimire; John A. Mayo; Maryellen S. Kelly; Kunning G. Xu; Tatyana A. Sysoeva (PLoS ONE, 2025)
Cold atmospheric pressure plasma (CAPP) is well documented to have microbicidal properties including against non-pathogenic Escherichia coli. In this feasibility study, a semi-quantitative method was developed to measure bactericidal activity of argon-CAPP (Ar-CAPP). Ar-CAPP susceptibility then was tested for a variety of clinically relevant E. coli strains, both uropathogenic E. coli (UPEC) and strains resistant to multiple antibiotics. All strains tested were found similarly susceptible to the antibacterial effects of Ar-CAPP. Next, methods were developed to propagate Ar-CAPP through defined lengths of plastic tubing with internal diameters ranging from 0.8 to 3.5 mm. Ar-CAPP propagated throughout all sizes of tubing tested, with visible plasma plumes exiting from the distal ends of the tubing. Bactericidal effects of the plasma efflux were tested against E. coli. Only partial loss of bactericidal activity was seen in tubing efflux plasma compared to control plasma jet plume unobstructed by tubing. Future work will develop bacterial biofilms on the internal surfaces of tubing to determine whether Ar-CAPP will ablate biofilms or kill biofilm bacteria. If successful, Ar-CAPP could further be tested for feasibility of disinfection of urinary catheters and other re-useable insertable medical devices in at-home and hospital settings.